Glory and identity in Pindar’s Nemean 10 - Bustos, María Natalia (CODEX - Revista de Estudos Clássicos, 2018)
The theme of “identity” in Pindar's Nemean 10 has been overlooked by scholars who have referred, especially, to the topics of friendship, loyalty and communication between men and god as essential topics of this Ode. This paper underlines the importance of the theme of “identity” in Pindar's Nemean 10. In this Ode, Pindar emphasizes that the innate traits and tradition that constitute the identity of a person or city are the result, not only of heritage, but also of the personal choices made in relation with other men and the gods. It also highlights the intervention of the gods in defining the identity of a person or city and in granting glory and immortality.